Charles Bonnet syndrome in adults with inherited retinal disease: prevalence and patient perspectives - Savita Madhusudhan; Thomas J M Weatherby; Matthew Boyle (BMJ Open Ophthalmology)
Objective To assess the prevalence of symptoms associated with Charles-Bonnet syndrome (CBS) in adult patients with inherited retinal disease (IRD) and explore patient perspectives and need for support.Methods and analysis This was a prospective single-centre cross-sectional service evaluation and improvement project that involved adult patients with a clinical diagnosis of IRD under the care of the specialist IRD service at a tertiary NHS healthcare provider in the UK. Information was gathered from a survey questionnaire completed by participants remotely or at a hospital appointment and electronic patient records.Results There were 103 surveys returned of which 94 were suitable for inclusion in the analysis. Visual hallucinations were reported by 18.6% of patients overall. Patients with visual acuity worse than 0.3 logMAR made up 76% of those reporting CBS symptoms.Of the patients who experienced visual hallucinations, 59% reported that their visual hallucinations had no effect on them, while 29% reported a negative effect, with 12% not commenting; only 12% said that they require further support.Conclusion CBS symptoms were reported by almost one in six patients in our IRD practice.Only a small proportion of patients included in this survey felt that they required additional support, but they did express that being informed early on of an explanation for their visual hallucinations was helpful.The limitations of our study are the small number of patients included in the survey, the lack of external validation of the questionnaire used, the risk of selection bias and the two different methods/phases of data collection used.